(untitled) (Fiep Bulletin - online, 2016)
Studies indicate that one of the benefits of physical exercise on the human body is the reduction of blood pressure. Heart rate exercisers is lower when compared with other untrained. The objective of this research was to measure the blood pressure and heart rate of praticiens of physical exercise in a gym in the city of Teresina. The sample selection was made through the pursuit of fitness evaluations in a gym in the northern area of Teresina-PI, consisting of 92 subjects of both genders, being, however, divided into two groups: group I, consisting of subjects with aged between 20 and 40 years, and group II containing a subject aged over 40 and under 90 years of age. Data analysis was performed using Microsoft Excel 2007 software version, using as measures: description in average, maximum and minimum values??. In sequence, arranging them in tabular form enabling better understanding of the provision and outcomes. The results show that the overall mean SBP and DBP is average and there were no significant differences between genders and age groups. The HR remained balanced between genders and age groups. We conclude that in the studied group exercise training seems to have favored the maintenance of desirable levels of blood pressure and heart rate.